PROFIL MAHASISWA PENGKONSUMSI MINUMAN KERAS DI KELURAHAN SIMAPANG BARU KECAMATAN TAMPAN PEKANBARU - Yusup Arifin; Swis Tantoro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research was conducted in the Simpang Baru District TampanPekanbaru aims to, which is : determine the characteristics of students drinkersbooze at the Simpang Baru District Tampan Pekanbaru. To know that whatever bethe causes of or it what the background of students do the activites of liquor. Thisresearch is Discrictive Qualitative residents and the seller alqoholic drimkstudents who duing activities of drinking alcohol. The techniques who used isSnowball Sampling is a determination sampels start from the number of small tobe. So sample used a technique Obsevations, the Decumentation, and in depthinterviews with using guidelines interviews in analyzing the data research resultson the use of the analysis Qualitative and in writing outlined in the descriptive.The results of this research can be countuded that the background of the studentsdrinking alcohol is the influence of the family environment and the influence offriends.The keyword : the profile of students, drink alcohol.